2016
DOI: 10.4103/0976-9668.175049
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of frequency of micronuclei in normal, potentially malignant diseases and oral squamous cell carcinoma

Abstract: Context:The assessment of micronuclei (MN) in exfoliated oral epithelial cells is a promising tool for the study of epithelial carcinogens and can be used to detect chromosome breakage or mitotic interference, thought to be relevant to carcinogenesis.Aims:To detect MN in exfoliated oral mucosal cells in individuals using various tobacco forms and also to detect frequency of MN in premalignant lesions and conditions (potentially malignant diseases [PMD's]) and oral squamous cell carcinoma (OSCC). To correlate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
4
15
0
Order By: Relevance
“…The results showed that the mean number of micronuclei in group III, i.e., subjects with combined habit (22.44 ± 9.84) was higher as compared with smokeless tobacco users (18.28 ± 10.00), tobacco smokers (11.38 ± 6.38), and control group (4.86 ± 2.49). Similar type of findings has been reported by Patel et al, 19 Palaskar and Jindal, 20 Bansal et al, 21 Motgi et al, 22 and Sangle et al 23 According to our results, the extent of genotoxic damage is more in smokeless tobacco users as compared with smoking tobacco. This may be explained by the fact that during chewing, mucosa is in direct contact with tobacco for a longer period of time as compared with smoking which may result in prolonged absorption of nitrosamines, and hence, considerably more nuclear and DNA damage.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that the mean number of micronuclei in group III, i.e., subjects with combined habit (22.44 ± 9.84) was higher as compared with smokeless tobacco users (18.28 ± 10.00), tobacco smokers (11.38 ± 6.38), and control group (4.86 ± 2.49). Similar type of findings has been reported by Patel et al, 19 Palaskar and Jindal, 20 Bansal et al, 21 Motgi et al, 22 and Sangle et al 23 According to our results, the extent of genotoxic damage is more in smokeless tobacco users as compared with smoking tobacco. This may be explained by the fact that during chewing, mucosa is in direct contact with tobacco for a longer period of time as compared with smoking which may result in prolonged absorption of nitrosamines, and hence, considerably more nuclear and DNA damage.…”
Section: Discussionsupporting
confidence: 92%
“…Collection of exfoliated cells [3] Subjects were asked to rinse their mouth gently with tap water before the start of the procedure. A slightly moistened wooden spatula was used to obtain the smear of exfoliated cells from the oral cavity (buccal mucosa in control group).…”
Section: Sample Collectionmentioning
confidence: 99%
“…[2] Most of the oral cancers are preceded by the potentially malignant disorders (PMD) that give a warning of risk and provide an opportunity for detection and preventive measures. [3] The possibility of malignant transformation of PMD is reported to be between 6.6% and 36.4%. [4] Early diagnosis may improve the survival and decrease the morbidity of patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations